The Formation of Social and Economic Peripheries in Hungary after the Change of Regime - Süli-Zakar, István (Acta Geographica Debrecina Landscape & Environment series, 2016)
The Hungarian industrial revolution started in the second half of the 19th century, which caused the revaluation of the geographical peripheries in Hungary. After the Trianon Treaty the rural areas of Hungary lost their foreign markets and became the "country of three million beggars". The socialist industrialization of the systems of Rákosi and Kádár absorbed the surplus of rural labour, but the industrialization meant the redistributive exploitation of the agricultural areas and the further impoverishment. After the political transition in 1989, the rural Hungary could not be the "pantry of the Council for Mutual Economic Assistance", and the final crisis of the Hungarian agricultural sales finalized the deformation of the three-quarters of Hungary, the major part of the rural areas in Hungary. In the recent decades the brain drain worked in the Hungarian peripheries, the disinvestment and the pauperization increased. The emerging of the new latifundia and the monoculture commodity production operate independently, separated from the Hungarian rural people in the sense of ownerships and production. As the result of these negative processes, significant part of the society in the peripheral areas declassed. In this hopeless situation awareness only a conscious regional policy and above all, a very well-considered education is only able to offer a chance for break.